Towards a model of integrated English language curriculum for secondary schools in Kenya - Okwara, Michael Okello; Shiundu, John O.; Indoshi, F. C. (Educational Research Review, 2009)
Design of the Integrated English Language Curriculum has been blamed for falling standards of students’ competence in the subject. Teacher input in the curriculum design has rarely been considered in the centralized curriculum development approach used in Kenya. However, it is now recognized that teacher input is critical if curriculum is to be effective. The purpose of this study was therefore to evaluate the implementation of the integrated approach to the teaching of English in secondary schools in Kenya and provide a proposal for a revised programme that takes into account teacher input which is often ignored in centralized curriculum development systems such as the one in Kenya. Data was collected from curriculum developers using an interview schedule and from teachers of English using a questionnaire. The study revealed that stakeholders perceived the integrated approach in conflicting terms and Teachers were not well prepared to implement the integrated approach. Curriculum developers advocated for the continuation of the integrated practice while teachers of English called for separation of English and Literature. A new shared integrated model is proposed. Key words: English language curriculum, integrated curriculum, challenges, opportunities
openalex: W2118498549 mag: 2118498549
Keywords: openalex:import